Reversible unity power factor step-up - Colling, I.E.
A reversible step-up/step-down AC-DC converter is presented in this paper. It is a fifth-order system, capable of managing power transfer from a DC source to an AC one, with any ratio between the DC and the AC voltage levels, and producing a sinusoidal output current, using only one power processing stage. By reversing the energy flow this circuit becomes a high power factor rectifier. This reversion can be obtained simply by inverting the reference AC current. The system is analyzed as the connection of two independent lower order subsystems, controlled by sliding mode with decentralised switching scheme. Experimental results from a 100 W prototype operating in both senses, as inverter and as rectifier, are shown to confirm the mathematical analyses and simulations
Keywords: 100 W; AC current control; DC-AC power conversion; Decentralised switching; Energy flow reversal; Fifth-order system; High power factor rectifier; Mathematical analyses; Power quality; Power supplies; Power transfer management; Reference AC current inversion; Reversible unity power factor converter; Sinusoidal output current; Sliding mode control; Step-up/step-down AC-DC converter; Variable structure systems